2017
DOI: 10.3390/polym9100526
|View full text |Cite
|
Sign up to set email alerts
|

Facile Cellulose Dissolution and Characterization in the Newly Synthesized 1,3-Diallyl-2-ethylimidazolium Acetate Ionic Liquid

Abstract: Abstract:A facile cellulose solvent 1,3-diallyl-2-ethylimidazolium acetate ([AAeim][OAc]) with high electrical conductivity has been designed and synthesized for the first time, via a quaternization reaction and ion exchange method. The dissolution characteristics of cellulose in this solvent were studied in detail. Meanwhile, the co-solvent system was designed by adding an aprotic polar solvent dimethyl sulfoxide (DMSO) in [AAeim] [OAc]. The effects of temperature and the mass ratio of DMSO to [AAeim][OAc] on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…However, above the 300°C, the stability of the chemically treated sample decreases compared with that of pure rice husk. This is attributed to the presence of lignin moieties in the pure sample, which confers better stability on them [27]. Surface morphologies of pure rice husk and the chemically treated Supplementary Figure 2c.…”
Section: Resultsmentioning
confidence: 98%
“…However, above the 300°C, the stability of the chemically treated sample decreases compared with that of pure rice husk. This is attributed to the presence of lignin moieties in the pure sample, which confers better stability on them [27]. Surface morphologies of pure rice husk and the chemically treated Supplementary Figure 2c.…”
Section: Resultsmentioning
confidence: 98%
“…The XRD patterns of cellulose regenerated using [Emim][Ac] showed that the main diffraction peak was shifted and widened at 2θ = 20.7° ( Figure 2 b). The existence of peaks at approximately 2θ = 20° suggested the conversion of crystal structure into amorphous state [ 41 , 43 , 44 ]. In contrast, the cellulose regenerated using alkali solutions including NaTU, TBAH, and TBPH displayed diffraction peaks at 2θ = 12.3°, 14–18°, 20.4°, and 22.3° corresponding to the cellulose II crystal structure [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Solvent‐based processes using milder conditions and focusing on the lignin removal are inter alia the organosolv and organocell process. Another possibility for cellulose dissolution directly from biomass could be the use of ionic liquids (IL), having been widely used for cellulose dissolution in recent years . In particular, ILs with strong hydrogen‐bond acceptors with anions such as chloride or acetate have shown the ability to dissolve cellulose under relatively mild conditions …”
Section: Lignocellulosic Biomassmentioning
confidence: 99%